Knowledge sharing behaviour in innovative working environment: A case of a software developing company - Ting, Hiram; Chuah, Chin Wei; De Run, Ernest Cyril (Medwell Publishing, 2016)
This study examines knowledge sharing behaviour in a highly innovative company.Particularly, the effect of key organizational factors, namely culture, trust, reward system, information system and structure on knowledge sharing is looked into. Team performance is also included as outcome construct to provide greater insights into the role of knowledge sharing.A quantitative approach via questionnaire-based survey was administered in a software development company in Malaysia.Data collected was then tested using correlation and regression analysis.The findings show that all organizational factors under investigation have positive effect on knowledge sharing and subsequently team performance.Despite being innovative and competitive, employees are willing to share knowledge mainly due to the culture, structure and information system of the organization